Examining the psychometric properties of the Coach-Athlete Relationship Questionnaire (CART-Q) with basketball players in China and Spain - Wang, Jingfei; Cordente-Martínez, Carlos; Ospina-Betancurt, Jonathan (Frontiers in Psychology, 2023)
The study examines the complex interactions between coaches and athletes in federative basketball in two different cultural contexts: China and Spain. The paper examines the interpersonal psychological dimensions from a direct viewpoint and a meta-perspective, drawing on the Coach-Athlete Relationship Questionnaire (CART-Q) and guided by the 3Cs model (Closeness, Commitment, and Complementarity). The CART-Q was translated and modified for use in both nations' federative basketball organizational systems to guarantee cross-cultural applicability. Careful translation techniques were used to achieve semantic homogeneity between the Spanish and Chinese versions of the questionnaire, including talks with knowledgeable linguists. The translated versions improved response comparability and kept the same item numbers as the original 2012 instrument. Out of the 771 distributed questionnaires, 763 legitimate answers were gathered via online surveys conducted using secure platforms (Google Forms for Spain and Wenjuanxing for China). The research included a three-step mediation study using structural equation modeling, which allowed for a thorough investigation of the concurrent validity of the modified CART-Qs. The findings indisputably support the reliability and validity of the CART-Qs translated into Chinese and Spanish. The research shows small but significant cultural disparities in the comprehensive perspective of coach-athlete interactions. These results have extensive ramifications for the sport and highlight how crucial it is to consider cultural differences when coaching and developing athletes.